Hypermetabolism and Coronavirus Disease 2019. Issue 7 (12th July 2020) - Yu, Pey‐Jen; Cassiere, Hugh; DeRosa, Sarah; Bocchieri, Karl; Yar, Shiraz; Hartman, Alan
Abstract: Background: Hypermetabolism has been described in stress states such as trauma, sepsis, acute respiratory distress syndrome, and severe burn injuries. We hypothesize that patients with Coronavirus disease 2019 (COVID‐19) may develop a hypermetabolic state, which may be a major contributing factor to the extraordinary ventilatory and oxygenation demands in patients with COVID‐19. Method: Resting energy expenditure (REE), carbon dioxide production (VCO2 ), and oxygen consumption (VO2 ) were measured by indirect calorimetry on 7 critically ill patients with COVID‐19. Results: The median measured REE was 4044 kcal/d, which was 235.7% ± 51.7% of predicted. The median VCO2 was 452 mL/min (range, 295–582 mL/min), and the median VO2 was 585 mL/min (range, 416–798 mL/min). Conclusion: Critically ill patients with COVID‐19 are in an extreme hypermetabolic state. This may explain the high failure rates for mechanical ventilation for these patients and highlights the potential need for increased nutrition requirements for such patients.